Public Transport Fleet Replacement Optimization Using Multi-Type Battery-Powered Electric Buses. Issue 12 (December 2021) - Tang, Chunyan; Li, Xiaoyu; Ceder, Avishai (Avi); Wang, Xiaokun
To achieve a green and sustainable public transit system, most transit agencies plan to completely replace current diesel and hybrid buses with battery-powered electric buses (EBs) in the decades ahead. Based on performances of EBs in practical operations, this study develops a transit fleet replacement model using multi-type EBs to determine an optimal fleet replacement plan in a cost-effective manner, considering associated diesel–electric replacement rates and in-vehicle crowd costs for passengers. Multi-type EBs include small EBs with fast charging technique, and large EBs with fast and slow charging techniques. The proposed model is applied to a real-life case study of the transit system in Qingdao, China. The results obtained indicate that large EBs with a high price tag are preferentially purchased in the first few years of the analysis period, whereas small EBs with a low price tag are favored in the latter years. The use of multi-type EBs results in a significant saving of the total cost, compared with the use of single-type EBs. Interestingly, with the increase of passenger demand, a large EB with a fast charging method presents more benefits than others. In contrast, a small EB has more advantages in a transit system with low demand.